2011
DOI: 10.1017/s1742758411000105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selection indices to identify sorghum genotypes resistant to the spotted stemborer Chilo partellus (Lepidoptera: Noctuidae)

Abstract: Abstract.The resistance or susceptibility of sorghum genotypes to damage by the spotted stemborer, Chilo partellus (Swinhoe) (Noctuidae: Lepidoptera) in sorghum is commonly measured in terms of leaf damage, deadheart formation and stem tunneling. Effect of the host plant on the insect survival and development (antibiosis), and the plant's response to insect damage (tolerance or recovery resistance) are also important parameters for measuring host plant resistance to stemborers. We compared 10 selection indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…The association between various damage traits and grain yield is useful for selecting superior genotypes. A number of parameters have been reported to be associated with resistance to spotted stem borer in sorghum because resistance is a quantitative trait and selection based on a single parameter is not efficient (Singh et al, 2011). In the present study sorghum genotypes showed difference in damage level in various damage traits and this results fall in line with findings of Sharma et al (2006) who reported a great variation in resistance levels between resistant and susceptible entries.…”
Section: Stem Tunnellingsupporting
confidence: 90%
See 1 more Smart Citation
“…The association between various damage traits and grain yield is useful for selecting superior genotypes. A number of parameters have been reported to be associated with resistance to spotted stem borer in sorghum because resistance is a quantitative trait and selection based on a single parameter is not efficient (Singh et al, 2011). In the present study sorghum genotypes showed difference in damage level in various damage traits and this results fall in line with findings of Sharma et al (2006) who reported a great variation in resistance levels between resistant and susceptible entries.…”
Section: Stem Tunnellingsupporting
confidence: 90%
“…In this study the entries selected as best registered lowest yield loss under infested and uninfested condition, which is on par with the resistant check, IS 2205 which was also supported by Singh et al (2011) who suggested that selection of genotypes should be based on grain yield losses under borer-infested and uninfested conditions.…”
Section: Grain Yield Performance Under Infested and Uninfested Conditionsupporting
confidence: 72%
“…The application of the liquid insecticide Karate was not proved to be responsive treatment. Similar results were obtained by Singh et al [36], who reported as a precise conclusion that liquid insecticides were less efficient than granular formulations.…”
Section: Effects Of Treatments On Crop Yieldsupporting
confidence: 90%
“…Drought tolerance was estimated based on the calculation of five different drought stress tolerance indices. Stress Susceptibility Index (SSI), Stress Tolerance Index (TOL), Modified Severity Stress Susceptibility Index (SSSI), Drought Yield Index (DYI), and Drought Tolerance Efficiency (DTE) (Fischer and Maurer, 1978;Fischer and Wood, 1981;Rosielle and Hamblin, 1981;Singh et al, 2011;Raman et al, 2012;). SSI = (1 -(Ys/Yp)) / (1 -(Ŷs/Ŷp)) Eq.1 TOL = Yp -Ys Eq.2 SSSI = (1 -(Ys/Yp)) -(1 -(Ŷs/Ŷp)) Eq.3 DYI = (Ys/Yp)/(Ŷs/Ŷp) Eq.4 DTE = (Ys / Yp) x 100 Eq.5 Yp = productivity in the control, Ys = productivity in the drought, Ŷp = mean of all varieties in the control treatment and Ŷs = mean of all varieties in the drought treatment, Eq.…”
Section: Tolerance Indices To Drought Stressmentioning
confidence: 99%